Biopsy proven fibroadenomas- how frequent is pathologies other than fibroadenomas post-excision? - Wahab, Tajudeen A; Uwakwe, Hanna; Aransi, Rilwan; Khan, Humuyan Kabir; Jumah, Maher (International Journal of Medicine, 2018)
Introduction: Breast fibroadenoma (FA) is a common benign tumour diagnosed usually through ‘Triple Assessment’. FA that is large, symptomatic or exhibit interval growth is recommended for excision. Some patients question the need for excision if preoperative assessment concluded FA while others want to be absolutely sure that the ‘FA’ that is not excised and managed conservatively is absolutely a FA. The aim of the present study is to ascertain the magnitude of unexpected post-excision pathology when a biopsy proven FA is excised according to the current UK guideline.Materials and Method: Retrospectively analysis of patients who underwent surgery for FA excision over a 3 year period. Data on patient demographics, ultrasound findings and size at diagnosis, any interval change in size, indication for excision were collected and pathology pre- and post-excision compared.Result: Of the 276 FA excised in 258 patients in 3years, a preoperative diagnosis of FA was confirmed in 251 cases while 25 breast lumps were excised based on the benign features on examination and imaging. The post excision histopathology confirmed the preoperative diagnosis of FA in 264 (95.7%), phyllodes in 8(3%) and 4 (1.3%) other pathologies.Conclusion: 4.3% of FA excised in our specialist unit after Triple Assessment returns pathology other than FA post-excision, mostly benign phyllodes. FAs should be managed conservatively after triple assessment but surgery should be offered if there is still any doubt as there is no absolute guarantee that the presumed FA is actually a FA. For medicolegal reasons and culture of openness, patients should be aware of this possibility especially if FA is managed conservatively.